ANTHROPOGENIC MODIFICATION OF LANDSCAPES AND SCIENTIFIC AND THEORETICAL ISSUES OF THEIR RESEARCH (Scientific journal of the Fergana State University, 2024)
The article covers scientific research on the impact of human activity on the components of landscapes, classification of landscapes according to the degree of anthropogenic change and modification, and information on the emergence of new qualities in the landscape as a result of the modification of landscapes under the influence of anthropogenic factors.